Iniquitous Growth - Magno, Alexander (Kasarinlan: Philippine Journal of Third World Studies, 2009)
Government policies have deepened rather than alleviated the iniquitous disposition of the Philippine economy. The tax structure is regressive. The policy of privatization has benefited holders of big capital while disabling the state from effectively exercising distributive and public welfare functions. A conservative strategy on the debt question eroded consumption across the board and prevented the allotment of the budget for social infrastructural investments.